(untitled) (Research, Society and Development, 2021)
Cement is the costlier component of concrete, and its productive process causes considerable environmental impact. Thus, alternatives are studied to reduce the amount of cement used. An option is the use of optimized grain size curves of aggregates, aiming to achieve a higher compactness of concrete. An ideal grain size distribution results in a higher mechanical resistance of concrete, providing a reduction in cost and consumption of materials, and, consequently, in environmental impacts. Therefore, the present study aims to improve the properties of conventional concrete through optimized grain size distributions. In this research, concrete was produced with binary mixtures with rolled pebbles from Belém region, in Pará state, and ternary mixtures of granitic crushed stone from the metropolitan region of Recife, in Pernambuco state, and concrete properties in the hardened state were studied. The mix design IPT/EPUSP method was used and grain size composition, unit weight, water absorption by capillarity, and compressive strength tests were performed. It was observed an increase in compressive strength with for higher fine contents. Furthermore, for both aggregates studied, there was no loss in strength with the lower amount of cement used, due to the increased compactness of the concrete, indicated by the unit weight of the aggregate mixture. Therefore, the optimization of the grain size composition of the coarse aggregate provided a reduction in the cement consumption for the same required strength and for both analysed aggregates.